(untitled) (Scientific journal of the Fergana State University, 2023)
The article discusses the issues of a comprehensive assessment of natural diversity, defines the content of the concept of "natural diversity" and provides criteria for selecting and substantiating indicators for assessing natural diversity. Quantitative indicators were used to assess natural diversity.